The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.jmedchem.7b01704
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Dimeric Lysine N-Alkylamides as Potent and Broad-Spectrum Antibacterial Agents

Abstract: Antibiotic resistance is one of the biggest threats to public health, and new antibacterial agents hence are in an urgent need to combat infectious diseases caused by multidrug-resistant (MDR) pathogens. Utilizing dimerization strategy, we rationally designed and efficiently synthesized a new series of small molecule dimeric lysine alkylamides as mimics of AMPs. Evaluation of these mimics against a panel of Gram-positive and Gram-negative bacteria including MDR strains was performed, and a broad-spectrum and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 70 publications
0
45
0
1
Order By: Relevance
“…It is accredited to most of the chemical and medicinal properties of the plant including pungency, tingling or burning sensation when the plant is eaten and Botox-like effects (Barbosa et al, 2016;Silveira et al, 2018). In view of the potentials of alkylamides as a source of novel antibiotics (Niu et al, 2018;Chakthong et al, 2019), this study adds to the compendium as A. oleracea extract was effective against a variety of pathogenic bacteria tested.…”
Section: Pb Lalthanpuii Et Al: Chemical Profiling Of Alkylamides Fmentioning
confidence: 97%
“…It is accredited to most of the chemical and medicinal properties of the plant including pungency, tingling or burning sensation when the plant is eaten and Botox-like effects (Barbosa et al, 2016;Silveira et al, 2018). In view of the potentials of alkylamides as a source of novel antibiotics (Niu et al, 2018;Chakthong et al, 2019), this study adds to the compendium as A. oleracea extract was effective against a variety of pathogenic bacteria tested.…”
Section: Pb Lalthanpuii Et Al: Chemical Profiling Of Alkylamides Fmentioning
confidence: 97%
“…In the United States, 2 million people get infected by antibiotic-resistant infections every year, which is estimated to cause more than 700,000 deaths (Nimmagadda et al, 2017;Wang et al, 2019). Over the last century Grampositive bacteria, especially the notorious methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus epidermidis (MRSE), and vancomycin-resistant E. faecal (VRE), have spread easily and are now becoming the leading cause of bacterial infections within both health-care and community settings (Lee et al, 2018;Niu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Méndez-Samperio, 2014;Teyssières et al, 2016) Previous reports have shown that HDPs, such as indolicidin (Galdiero et al, 2016) and human defensin 5 (Lei et al, 2018), are potential antibiotics based on their membrane disruption (permeabilization and lysis) ability. Unlike conventional antibiotics targeting some specific intracellular and cell wall targets, the main driving force in the selectivity is the electrostatic interaction between HDPs and bacterial membrane (Su et al, 2017;Niu et al, 2018). It is well known that the membrane of bacteria is negatively charged due to the presence of phosphatidylglycerol (PG), whereas mammalian cell membrane consists of zwitterionic sphingomyelin and phosphatidylcholine (PC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations